Legal Protection of Sharia Investors in Indonesia: A Maqāṣid-Based Critique and Comparative Study of Malaysia’s System: Perlindungan Hukum Investor Syariah di Indonesia: Studi Kritis Maqāṣid dan Perbandingan Sistem Malaysia - Isnaini, Suhaebatul; Luthfi, A Hashfi; Ramdhani, Fajri Zulia (Sharia and Law Faculty of Sunan Kalijaga Islamic State University Yogyakarta, 2024)
Abstract: This study analyzes the effectiveness of legal protections for Sharia sukuk investors in Indonesia, particularly in the Sukuk Tabungan ST012 instrument, based on the newly issued Financial Services Authority (OJK) Regulation No. 22 of 2023. The research is under a normative legal method combined with conceptual analysis using the Maqāṣid Ash-Sharīʿah framework developed by Auda. The findings indicate that the regulation introduces key elements such as strengthened literacy, transparency, and governance. However, the regulation’s effectiveness remains limited in safeguarding investor capital, ensuring rational decision-making, and providing psychological security. The Maqāṣid-based analysis reveals that the dimension of ḥifẓ al-māl (protection of wealth) is not yet fully integrated into policy design. A comparative analysis with Malaysia highlights Indonesia’s structural weaknesses, particularly the non-binding nature of fatwa authorities and the lack of legal certainty in Sharia supervision. This study recommends strengthening Sharia authority systems and integrating Maqāṣid values into the national regulatory framework. The study is limited by its non-empirical approach and narrow focus on a single instrument. Future research could consider quantitative methods and undertake broader cross-country regulatory comparisons. Abstrak: Studi ini menganalisis efektivitas perlindungan hukum bagi investor sukuk syariah di Indonesia, khususnya pada instrumen Sukuk Tabungan ST012, berdasarkan Peraturan Otoritas Jasa Keuangan (OJK) Nomor 22 Tahun 2023 yang baru diterbitkan. Penelitian ini menggunakan metode hukum normatif yang dikombinasikan dengan analisis konseptual menggunakan kerangka Maqāṣid Ash-Sharīʿah yang dikembangkan oleh Auda. Hasil penelitian menunjukkan bahwa peraturan tersebut memperkenalkan unsur-unsur kunci seperti peningkatan literasi, transparansi, dan tata kelola. Namun, efektivitas peraturan tersebut masih terbatas dalam melindungi modal investor, memastikan pengambilan keputusan yang rasional, dan memberikan keamanan psikologis. Analisis berbasis Maqāṣid mengungkapkan bahwa dimensi ḥifẓ al-māl (pelindungan harta) belum sepenuhnya terintegrasi dalam desain kebijakan. Analisis perbandingan dengan Malaysia menyoroti kelemahan struktural Indonesia, terutama sifat tidak mengikat dari otoritas fatwa dan ketidakpastian hukum dalam pengawasan syariah. Studi ini merekomendasikan penguatan sistem otoritas syariah dan integrasi nilai-nilai Maqāṣid ke dalam kerangka regulasi nasional. Studi ini dibatasi oleh pendekatan non-empiris dan fokus yang sempit pada instrumen tunggal. Penelitian masa depan dapat mempertimbangkan metode kuantitatif dan melakukan perbandingan regulasi lintas negara yang lebih luas.